Weight cycling of athletes and subsequent weight gain in middleage - Saarni, S. E.; Rissanen, A.; Sarna, S.; Koskenvuo, M.; Kaprio, J. (International Journal of Obesity, 2006)
To study the effects of repeated cycles of weight loss and regain as young adults on long-term weight development.Design:A follow-up study with questionnaires in 1985, 1995 and 2001.Setting:Finland.Subjects:A national cohort of 1838 male elite athletes who had represented Finland in major international sport competitions in 1920-1965, including 370 men engaged in sports in which weight-related performance classes are associated with weight cycling (boxers, weight lifters and wrestlers; further called as weight cyclers), and 834 matched control men with no athletic background.Outcome measure:Weight change since the age of 20 years, body mass index (BMI) and prevalence of obesity and overweight.Results:The weight cyclers gained 5.2 BMI units from age 20 years to their maximum mean weight, which was at age 58.7 years. Corresponding figures for the controls were 4.2 BMI units at 58.5 years and for other athletes 3.3 BMI units at age 62.5 years. The proportion of obese (BMI>/=30 kg/m(2)) subjects was greatest among the weight cyclers both in 1985 and 1995. In 2001, the weight cyclers were more often obese than other athletes, but did not differ from the controls. The odds ratio for the weight cyclers to be obese compared to other athletes in 1985 was 3.18 (95% confidence intervals 2.09-4.83), and compared to the controls 2.0 (1.35-2.96). The enhanced weight gain of the weight cyclers was not accounted for by present health habits (smoking, alcohol use, use of high-fat milk or physical activity) or weight at age 20 years.Conclusions:Repeated cycles of weight loss and regain appear to enhance subsequent weight gain and may predispose to obesity. Chronic dieting with weight cycling may be harmful for permanent weight control.